Diffuse Large B-Cell Lymphoma: Clinical Presentation and Treatment Outcomes From the OncoCollect Lymphoma Registry - Nair, Reena; Bhurani, Dinesh; Rajappa, Senthil; Kapadia, Asha; Reddy Boya, Rakesh; Sundaram, Subramanian; Menon, Hari; Raman, Ganapathi S.; Seshachalam, Arun; Nimmagadda, Ramesh (Frontiers in Oncology, 2022)
Background: In an earlier study conducted between 2005 and 2009 diffuse large B-cell lymphoma [DLBCL] was the commonest subtype of lymphoma, standard CHOP was the treatment of choice, 42% patients received rituximab and 29% patients were lost to follow up during therapy. The OncoCollect Registry was set up in 2017 to address the challenges in the collecting retrospective data through chart review, recording access to anthracycline and rituximab-based treatment, and to study outcomes and any improvement in the patient follow up. Methodology: OncoCollect Lymphoma group registry was established at a national level with 9 participating centers. Lymphoma patients registered at these centers between 2011 to 2017 were included. The clinical features, prognostic stratification, associated co-morbidities, response to 1st line treatment and 3-year outcomes of adult patients with DLBCL were analyzed. Results: Of the 5886 lymphoma patients registered in the OncoCollect registry, 2581 (44%) had DLBCL. 1961 were evaluable for frontline therapy. The median age at presentation was 57 years. Gender ratio (M:F) was 1.6:1. At presentation: 43% were early stage, 70% had low and low intermediate IPI, 53% had extra-nodal disease and 30.9% had one or more co-morbidities (data available for 1136 patients). The commonest extra nodal site was gastro-intestinal (23.98%) followed by head and neck (19.24%). The overall response rate was 79.29%. Complete remission was seen in 61.75%, partial response in 17.5%, stable disease in 4.3% and progressive disease in 8.47%. Patients who received anthracycline based therapy (86.7%) and rituximab-based therapy (83.7%) had a 3-year Event Free Survival (EFS) of 69.67% and 68.48% respectively. With a median follow-up of 33 months the 3-year Overall Survival (OS) and EFS were 75.37 % and 66.58 % respectively. Conclusions: DLBCL remains the commonest (44%) lymphoma subtype and is curable with standard anthracycline and rituximab-based therapies. The availability of rituximab has increased the proportion of patients receiving standard chemoimmunotherapy.